Materiality and Aesthetics in Archaic and Classical Greek Poetry - Lather, Amy (Edinburgh University Press, 2021)
Materiality and Aesthetics in Archaic and Classical Greek Poetry -- Copyright -- Contents -- List of Illustrations -- Acknowledgements -- Note on the Text -- Introduction -- 1 A Beautiful Mind: Patterns of Thought and the Decoration of Textiles -- 2 Brazen Charm: The Vitality of Archaic Armour -- 3 Mind Tools: Art, Artifice and Animation -- 4 The Protean Shape of Lyric Poikilia -- 5 Metis and the Mechanics of the Mind -- 6 The Materiality of Feminine Guile -- Conclusions -- Bibliography -- Index Locorum -- Subject Index.